Plasma electrolytic oxidation thermal barrier coating for reduced heat losses in IC engines. (September 2021) - Hegab, Abdelrahman; Dahuwa, Kamal; Islam, Reza; Cairns, Alasdair; Khurana, Ankit; Shrestha, Suman; Francis, Robin
Highlights: Plasma Electrolytic Oxidation (PEO) coating has been applied to IC engine piston. Thermo-swing effect of PEO enables rapid change of the coated surface temperature. Reduced heat loss with PEO piston coating improves engine indicated efficiency. High surface roughness of PEO coating negatively affects the insulation performance. Engine with PEO piston coating produces higher NOx and lower HC emissions. Abstract: The work involved the development and on-engine testing of a new "thermo-swing" barrier coating for reduced wall heat transfer and increased thermal efficiency in future diesel engines utilizing aluminium alloy pistons. Such swing coatings, of low thermal conductivity and low specific heat capacity, have recently been proposed to produce a dynamic thermal barrier layer that rapidly changes the temperature of the upper surface of the piston crown in response to the adjacent in-cylinder gas temperature. The new coating tested in this work was formed directly from the piston substrate material using an optimised plasma electrolytic oxidation process, with a silica top coat subsequently applied to entrap air within coating pores. Benchtop laser flash measurements were undertaken to quantify coating thermal properties and provide the required empirical data for future thermal simulation. Coatings of varying features were tested in a bespoke thermodynamic single cylinder diesel engine instrumented for precision measurements of in-cylinder pressure, fuel consumption and legislated engine-out emissions. The optimum coating applied across the full piston crown and bowl enabled up to 3% improvement in indicated thermal efficiency under idealised part load operating conditions. The coating reduced heat transfer during combustion, leading to elevated engine-out NOx. By retarding combustion phasing slightly from the optimum, the NOx increase could be mitigated while still retaining most of the fuel consumption benefit, with the remaining benefit associated with reduced heat transfer during the remaining power stroke. The emissions of other key pollutants (CO, unburned hydrocarbons and soot) were less affected under the part load conditions tested.